COMMUNICATION OF THE COVID-19 TASK FORCE IN INCREASING PUBLIC COMPLIANCE WITH HEALTH PROTOCOL IN PEKANBARU CITY - Suci Shinta Lestari; Nurazizah Rahma; Welly Wirman; Tantri Yazid (Indonesian Journal of Social Sciences, Policy and Politics, 2023)
The people of Indonesia and even the world are faced with an outbreak of a dangerous, contagious, and deadly virus called Corona Virus Disease 2019 (Covid-19). Its presence has been around for quite a while, starting in 2019 and now having developed into the Omicron Variant, which was first detected in South Africa (https://www.bbc.com). This research uses a qualitative type of research with a focus on studies, especially on how the communication used by the Pekanbaru City COVID-19 handling task force improved community compliance to comply with health protocols. Qualitative methods are research procedures that produce descriptive data in the form of written or spoken words from people and observable behaviors. The results of this study indicate that the Task Force for Handling COVID-19 has a variety of strategies and patterns to perform functions both preventive and persuasive to residents. In addition to communicating with the community, the Task Force also formed an organizational structure to support the implementation of various programs, one of which was resilient villages. This structure involves the central government, local governments, in this case the mayor, and his ranks.